The Notorious Voice of OpenAI ChatGPT in Finishing an Essay Writing Task in English Class - Mahmudah, Khotimah; Mardiana, Rizdika; Supraptiningsih, Nurhandayani; Rakerda, Hilda (JR-ELT (Journal of Research in English Language Teaching), 2025)
This study explores the role of ChatGPT as a writing assistance tool in English essay writing tasks among second-year EFL students. Triggered by discrepancies between assignment quality and in-class performance, the study investigates how students use, perceive, and critically evaluate ChatGPT. Using a descriptive qualitative approach, data were collected through a 30-item Likert-scale questionnaire distributed to 35 students. Based on data, 84.8% of students reported using Google Translate more frequently than ChatGPT, and only 18.2% admitted full reliance on ChatGPT for essay tasks. Over half of the students expressed scepticism about ChatGPT's grammatical reliability, and many found its writing style rigid. The findings reveal that while ChatGPT is widely known and occasionally used, students still rely more on tools like Google Translate and do not fully depend on ChatGPT.